How the Existence of International Public Policy in the Economic Field in the Implementation of a Policy in Indonesia - Devana Ardelia Najlaa; Chika Afifah Suwandi; Diane Wimas Enjella; Afina Anindita Ektya Putri; Nabila Mazidatul Maftuhah; Aulia Ramadhani Adila (Proceeding International Conference Restructuring and Transforming Law, 2022)
Public policy implementation is the implementation of a public policy through action in a way that is related to certain policies. Compiling this paper aims to discuss the concept of national and international public policy. By compiling this paper, it is possible to use the main sources from various literatures and significant discussions with the implementation of public policies, which have been complemented by the author's ideas on the given theme. As a result of this discussion, it has been determined that the implementation of public policy has been influenced by a number of factors including: aspects of authority, resources, and communication.In this application international economic policy is a science that examines how scarce resources are distributed to meet the needs of human life on a global scale. Indonesian economic policy or economic policy (economic policy) is a method of action taken by the government to regulate the country's economy to achieve certain goals